Enhancing Data Quality and Integrity in Machine Learning Pipelines: Approaches for Detecting and Mitigating Bias (International Journal of Scientific Research and Management (IJSRM), 2022)
Machine learning (ML) has become a cornerstone of innovation in numerous industries, including healthcare, finance, marketing, and criminal justice. However, the growing reliance on ML models has revealed the critical importance of data quality and integrity in ensuring fair and reliable predictions. As AI technologies are deployed in sensitive decision-making areas, the presence of hidden biases within data has become a major concern. These biases can perpetuate systemic inequalities and result in unethical outcomes, undermining trust in AI systems. The accuracy and fairness of ML models are directly influenced by the data used to train them, and poor-quality data—whether due to missing values, noise, or inherent biases—can degrade performance, skew results, and exacerbate societal inequalities. This paper explores the complex relationship between data quality, data integrity, and bias in machine learning pipelines. Specifically, it examines the different types of bias that can emerge at various stages of data collection, preprocessing, and model development, and the negative impacts these biases have on model performance and fairness. Furthermore, the paper outlines a range of bias detection and bias mitigation techniques, which are essential for developing trustworthy and ethical AI systems. From data preprocessing methods like imputation and normalization to advanced fairness-aware algorithms and post-processing adjustments, several approaches are available to improve data quality and eliminate bias from machine learning pipelines. Additionally, the paper emphasizes the importance of ongoing monitoring and validation of ML models to detect emerging biases and ensure that they continue to operate fairly as they are exposed to new data. The integration of regular audits, fairness metrics, and data drift detection mechanisms are discussed as crucial steps in maintaining model integrity over time. By focusing on the processes and strategies required to enhance both data quality and integrity, this paper aims to contribute to the development of more equitable, transparent, and reliable AI systems. The goal is to ensure that machine learning technologies can be used responsibly and in ways that promote fairness, equality, and trust, ultimately benefiting all sectors of society.